BESARAN STOK CADANGAN BERAS UNTUK INDONESIA - M. Husein Sawit (Agro Ekonomi, 2004)
Almost all Asian countries, including Indonesia, adopt rice reserve stock policy. The purpose of the policy is to reduce food insecurity risk due to natural calamity and man-made disaster, as well as to stabilize rice price. In the last 20 years, Bulog has maintained rice reserve stock to I million tons for those purposes. The last few years, the environments have changed rapidly due to expanding of transportation and telecommunication, rice trade now has became more transparent, and market information more perfectly. Rice policy in Indonesia has also changed rapidly since 1998. The objective of this paper is to evaluate the optimum size of rice reserve for Indonesia by applying 3 approaches, namely, NFA (National Food Authority) of the Philippines, Stock to Utilization Ratio of FAO, and Usual Marketing Requirement. It is found that the size of rice reserve should be 0.75 million tons at the lowest and 3.4 million ton at the highest. The results were compared to rice released for emergency and price stabilization purposes by Bulog, and released for emergency purposes by NGO, and bilateral (G to G. It is concluded that Indonesia only needs 0.750 million tons of rice for reserve stock. This size of reserve includes rice reserve stock for East Asian/ Asean Rice Reserve System.